LUBUKLINGGAU DURING THE RULE OF THE SINDANG KELINGI ILIR CLAN FROM 1855 TO 1942: Lubuklinggau Masa Pemerintahan Marga Sindang Kelingi Ilir Tahun 1855-1942 - Yadri Irwansyah; Suryani; Ira Miyarni Sustianingsih (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The purpose of this study is to discuss Lubuklinggau during the governance of the Sindang Kelingi Ilir Marga (clan) from 1855 to 1942. The background of this research focuses on the history of the formation of the Sindang Kelingi Ilir Marga and the political conditions in Lubuklinggau during its administration.The method used in this research is the historical method, which includes the stages of heuristics, criticism, interpretation, and historiography.Based on the findings and discussion, it can be concluded that the formation of the Sindang Kelingi Ilir Marga was driven by the implementation of the Simbur Cahaya Law in 1854. According to this law, the Dutch colonial administration required indigenous community units or hamlets under the Palembang Residency that had not yet formed a marga to immediately establish one. Therefore, starting in 1855, many new marga were established, including the Sindang Kelingi Ilir Marga, which was centered in the village of Lubuklinggau.As for the political situation in Lubuklinggau during the administration of the Sindang Kelingi Ilir Marga from 1855 to 1942, it was led by seven depati (traditional leaders) and one pesirah (head of the marga). Significant political development occurred during the leadership of Depati Ramitan (1916–1936). During his leadership, Lubuklinggau, as the center of the Sindang Kelingi Ilir Marga, was designated as the capital of the Onder Afdeeling Moese Oeloe (a Dutch colonial administrative division), replacing Muara Beliti in 1934. This change was supported by the development of various infrastructure projects in Lubuklinggau, such as highways and a railway line, which were inaugurated during Depati Ramitan’s administration.